Blood loss and transfusion risk in robotic‐assisted knee arthroplasty: A retrospective analysis. Issue 6 (27th July 2021) - Khan, Hasaan; Dhillon, Kieran; Mahapatra, Piyush; Popat, Ravi; Zakieh, Omar; Kim, Woo Jae; Nathwani, Dinesh
Abstract: Background: The purpose of this study was to compare total blood loss and the risk of receiving a blood transfusion in robotic‐assisted total knee arthroplasty (TKA) and unicompartmental knee arthroplasty (UKA) against conventional jig‐based techniques. Methods: Robotic TKA ( n  = 50) and UKA ( n  = 50) patients were matched to contemporary controls for TKA ( n  = 50) and UKA ( n  = 50) and retrospectively analysed. Results: Robotic TKA patients experienced 23.7% less blood loss compared to conventional TKA patients (911.0 ml vs 1193.7 ml, p  < 0.01), and were associated with an 83% relative risk reduction of receiving a transfusion (2% of patients vs 12%, p  = 0.02). Robotic UKA patients did not demonstrate less blood loss compared to corresponding controls (821.7 ml vs 854.7 ml, p  = 0.69). Both UKA groups received no transfusions. Conclusions: Robotic surgical systems in TKA reduces blood loss and lowers the risk of requiring a blood transfusion. In UKA, robotic‐assisted arthroplasty did not reduce blood loss compared to conventional arthroplasty.